2020
DOI: 10.22159/ajpcr.2020.v13i12.39557
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Anxiolytic Activity of Ethanolic Extract of Root of Acorus Calamus in Albino Mice

Abstract: Objective: Anxiety is classified as a form of sub-acute or chronic fear. Root of Acorus calamus has been traditionally used as an anxiolytic. The aim of the study is to assess the anxiolytic activity of ethanolic extract of A. calamus (EEAC) by elevated plus-maze test on Albino mice. Methods: Albino mice of either sex were taken and divided into five groups, each consisting of 5 mice. One group was used as control, one as standard (diazepam), and three as test groups treated with 100, 200, and 400 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Recent studies have demonstrated that the plant possesses anxiolytic activity on albino mice, which was evaluated using the ethanol extract showing an effective dose at 200 mg/kg body treatment. 25 In line with this and several other previous studies, the test doses for the administration were chosen to be 100 and 200 mg/kg body weight. In the MES model at dose of 200 mg/kg of methanolic extract of Acorus calamus leaves (T1) there was no significant anticonvulsant activity when compared to that of the control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that the plant possesses anxiolytic activity on albino mice, which was evaluated using the ethanol extract showing an effective dose at 200 mg/kg body treatment. 25 In line with this and several other previous studies, the test doses for the administration were chosen to be 100 and 200 mg/kg body weight. In the MES model at dose of 200 mg/kg of methanolic extract of Acorus calamus leaves (T1) there was no significant anticonvulsant activity when compared to that of the control.…”
Section: Discussionmentioning
confidence: 99%
“…But combination of the standard drug, sodium valproate at a dose of 100 mg/kg and methanolic extract of Acorus calamus leaves at a dose of 100mg/kg (T2), showed statistically significant reduction in the duration of Tonic Hindlimb Extension when compared to that of the control. 25 . In the PTZ model, a combination of the standard drug sodium valproate at a dose of 100 mg/kg and methanolic extract of Acorus calamus leaves at a dose of 100mg/kg (T4) showed significant anticonvulsant activity when compared to that of the control.…”
Section: Discussionmentioning
confidence: 99%
“…Several West African medicinal plants are used for the treatment of SBE in different communities [25] . Typically, aqueous or ethanolic plant extracts are administered orally, chewed, inhaled or applied topically at the site of a bite to neutralize the toxic effects of the offending snake venom, [80] Supporting Information, Table S1.…”
Section: Venom‐neutralising Potential Of West African Medicinal Plantsmentioning
confidence: 99%
“…In view of the fact that plant‐derived natural products or their scaffolds feature often in many pharmaceuticals, it is conceivable that the huge library of plant‐derived medicinal compounds if explored, can deliver the next generation of therapeutics to combat the lethality of SBE. As such, the search for antivenin medicinal plants or plant‐derived metabolites that can address the perennial burden of SBE has therefore been an active research area in many academic laboratories, [24–28] especially in regions where the burden of the disease is enormous.…”
Section: Introductionmentioning
confidence: 99%
“…13 The extracts are believed containing secondary metabolites such as alkaloids, tannins, flavonoids, steroids, and phenols. 14 The parts of the plant known to be used for the preparation of AgNPs are fruit, 15 leaves, and seeds. Since fruit contains high secondary metabolites, fruit is widely used in the preparation of AgNPs.…”
Section: Introductionmentioning
confidence: 99%